1992
DOI: 10.1002/jlac.199219920107
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of 4‐Oxoalkanoic Acids, 4. Synthesis of (±)‐6‐Alkyl‐5‐oxa‐1‐azabicyclo[4.3.0]nonan‐9‐ones, (±)‐5‐Alkyl‐4‐oxa‐1‐azabicyclo[3.3.0]octan‐8‐ones, and Substituted 1,6‐Dioxa‐3,8‐diazacyclodecanes by Reaction of Ethyl 4‐Oxoalkanoates with 3‐Aminopropanol and 2‐Aminoethanol

Abstract: Ethyl 4-oxoalkanoates 1 react at ambient temperature in dry methanol in the presence of molecular sieve 3 A in almost quantitative yield with 3-aminopropanol and 2-aminoethanol to form the bicyclic lactams rac-2 and rac-3, respectively. Owing to their carbon skeleton, ethyl 4-oxoalkanoates 1 are interesting starting materials for the synthesis of 1,4-diketones and, thus, of furans2x3), pyrroles4), and 2,3-dialkylcyclopent-2-en-1-ones'). Formally, the conversion of 1 into 1,4-diketones requires the nucleophilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The following observations are also worthy of note. It has been reported in the literature19 that the product of the reaction shown in entry 1, readily opens and reacts intermolecularly to form the centrosymmetric dimer under aqueous acidic conditions (Scheme ). We found this to be true (indeed, it also applied to other more heavily substituted products, although to a lesser extent), but we also found that this undesired dimerization could be avoided by moderating the amount of TFA employed in the cyclization step, and, in the most vulnerable cases, by neutralizing this TFA with Et 3 N prior to concentration of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…The following observations are also worthy of note. It has been reported in the literature19 that the product of the reaction shown in entry 1, readily opens and reacts intermolecularly to form the centrosymmetric dimer under aqueous acidic conditions (Scheme ). We found this to be true (indeed, it also applied to other more heavily substituted products, although to a lesser extent), but we also found that this undesired dimerization could be avoided by moderating the amount of TFA employed in the cyclization step, and, in the most vulnerable cases, by neutralizing this TFA with Et 3 N prior to concentration of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…The filtrate was concentrated under reduced pressure, and the resulting liquid was vacuum distilled (71−73 °C, 1 mmHg) to afford 3.86 g (40%) of (±)- 1j ‘ as clear, colorless liquid. For the known , racemic saturated bicyclic lactam ((±)- 1j ‘) (7a RS )-5-oxo-7a-methyl-2,3,5,6,7,7a-hexahydropyrrolo[2,1- b ]oxazole: R f 0.14 (1:1 EtOAc/hexanes); bp 71−73 °C, 1 torr; 1 H NMR (300 MHz, CDCl 3 ) δ 3.94 (m, 3H), 3.13 (m, 1H), 2.68 (m, 1H), 2.45 (m, 1H), 2.16 (m, 2H), 1.40 (s, 3H).…”
Section: Methodsmentioning
confidence: 99%
“…The following observations are also worthy of note. It has been reported in the literature [19] that the product of the reaction shown in Entry 1, readily opens and reacts intermolecularly to form the centrosymmetric dimer under aqueous acidic conditions (Scheme 3). We found this to be true (indeed, it also applied to other more heavily substituted products, although to a lesser extent), but we also found that this undesired dimerisation could be avoided by moderating the amount of TFA employed in the cyclisation step, and, in the most vulnerable cases by neutralising this TFA with NEt 3 prior to concentration of the sample.…”
mentioning
confidence: 99%